Between technologies, risks and uncertainties: possible paths for environmental labor law - Wünsch, Guilherme (2023)
This article deals with the impacts of new technologies on the environment, health and safety at work. The world of work, as well as society as a whole, faces a moment of profound and intense changes, driven mainly by technological progress. With regard to (Environmental) Labor Law, the technological tools and the impacts of their massive insertion in labor relations, subvert the industrial and concrete logic, closely linked to damage and its knowledge, with which issues were thought and regulated relating to the environment, health and safety at work. It is concluded that there is a need to offer efficient responses, bringing balance to the work environment and, above all, safeguarding fundamental rights.